The role of King III report on corporate governance in improving poor service delivery in the - Mokgopo, T. I. (My University, 2016)
When the new government came in to power in 1994 it inherited dysfunctional municipalities. In fact it inherited a country with high levels of poverty, growing levels of inequality and also social dysfunctionality. As such in an attempt to redress apartheid legacies, the new government reformed previous legislation and policies to address issues pertaining to segregation, inequity, inequality, discrimination, poverty and to establish new transitional local authorities. Therefore new institutions have been created with new principles, philosophies and support mechanisms to make the transformation of local government a success. This is irrespective of the government coming up with good policies and laws the South African local government sphere is still rocked by poor service delivery in the majority of the municipalities including the big metropolitan municipalities. Since 2008, South Africa has witnessed many service delivery protests by communities demanding better services. This article critically analyses the role of the King III report on corporate governance in improving poor service delivery in South African local government and to assess if indeed these policies and legislations can improve service delivery. The findings in this article indicates that corporate governance principles are an effective instrument in improving municipalities in South Africa and if adhered to by the municipal councils and management of all municipalities then the challenges that are faced at the local government will be minimised. This article further finds that the only way to restore public confidence in South Africa is by first fixing the local government as it is a test of the country as to whether it is able to manage its affairs and providing services to the members of the communities (public).
Published in: Journal of Public Administration and Development Alternatives. Vol. 1, No.1, July 2016. p. 77-89
Keywords: Corporate governance; Local governance - South Africa